The Cre1 and Cre3 Nematode Resistance Genes Are Located at Homeologous Loci in the Wheat Genome - John de Majnik; Francis C. Ogbonnaya; Odile Moullet; Evans S. Lagudah (Molecular Plant-Microbe Interactions, 2003)
Differential responses in host-nematode pathotype interactions occur in wheat lines carrying different cereal cyst nematode resistance (Cre) genes. Cre1, located on chromosome 2B, confers resistance to most European nematodes and the sole Australian pathotype, while Cre3, present on chromosome 2D, is highly resistant to the Australian patho-type and susceptible to a number of European pathotypes. Genes encoding nucleotide binding site-leucine rich repeat (NBS-LRR) proteins that cosegregate with the Cre3 locus cross hybridize to homologues whose restriction fragment length polymorphism (RFLP) patterns distinguish near-isogenic Cre1 nematode-resistant wheat lines. Genetic mapping showed that the NBS-LRR gene members that distinguished the Cre1 near-isogenic lines were located on chromosome 2BL at a locus, designated Xcsl107, that cosegregates with the Cre1 locus. A haplotype of NBS-LRR genes from the Xcsl107 locus provides a diagnostic marker for the presence of Cre1 nematode resistance in a wide collection of wheat lines and segregating families. Genetic analysis of NBS-LRR haplo-types that cosegregate with Cre1 and Cre3 resistance, together with flanking cDNA markers and other markers from homoeologous group 2 chromosomes, revealed a conserved gene order that suggests Cre1 and Cre3 are homeoloci.